Spectrophotometric analysis of magnetic white dwarf: I. Hydrogen-rich compositions - François, Hardy von; Dufour, Patrick; Jordan, Stefan (Monthly notices of the Royal Astronomical Society, 2023)
We present a homogeneous analysis of all DA stars labelled as magnetic in the Montreal White Dwarf Database. Our sample is restricted to almost all known magnetic white dwarf showing clear sign of splitting (B ≳ 1-2 MG) that have parallax measurements from the second Gaia data release, photometric data from diverse surveys and spectroscopic data from Sloan Digital Sky Survey or archival data from the Montreal group. We determine the atmospheric parameters (effective temperature, surface gravity, and magnetic field strength/geometry) of all objects using state-of-the-art model atmosphere/magnetic synthetic spectra, as well as reclassify many objects that were prematurely labelled as potentially magnetic. Finally, we discuss the atmospheric parameters/field properties distribution as well as the implication on our understanding of magnetic white dwarfs origin and evolution.